Taxation for executors and trustees - Mellows, Anthony R. (London : Butterworths, 1976)
The main new features of this edition of this book are the inclusion of chapters on capital transfer tax and development land tax.
Includes index.
osc 30/06/2017
Loans
Keywords: Decedents' estates; Taxation; England